Acrometastasis to the finger from hepatocellular carcinoma mimicking a glomus tumour: A case report - Hari Prasad V; Philip P. Puthumana; Joji Krishnan (Journal of Orthopaedic Reports)
Background: Acrometastasis refers to the uncommon phenomenon of metastasis occurring to distal part of extremities from different primary malignancies predominantly lungs, breast, and thyroid. Digital acrometastases to fingers as a presentation of hepatocellular carcinoma (HCC) are extremely rare. Case presentation: A 70-year-old male patient presented to the orthopaedic casualty with a history of fall and sustained a supracondylar fracture of the humerus which was treated conservatively. Incidentally, the patient was noted to have a swelling of the left ring finger with a history of bleeding. A provisional diagnosis of glomus tumour was made. Imaging studies of the left hand were suggestive of a large glomus tumour/malignant neoplasm with destruction of the underlying phalanx. The lesion over the fingertip was excised and histopathological examination revealed a metastatic tumour which was confirmed to be hepatocellular carcinoma. Conclusions: This case report presents an unusual and rare presentation of HCC and reiterates the need to have a high index of suspicion while treating atypical lesions in the hands.